Evolution of professional identity: the Dnipro School of Dermatovenereology in the XX-XXI centuries - Sviatenko , T.V.; Zakharov , V.K.; Zakharov , S.V.; Striukov , V.V.; Bashmakov , D.H.; Gorbuntsov, V.V.; Pohrebniak, L.A.; Akymova , V.V. (Medicni Perspektivi, 2025)
The purpose of the study is a historical analysis of the Dnipro School of Dermatovenereology through the prism of the philosophy of science, identification of key periods of its formation and development, main achievements, and the role of leaders in the formation of the scientific school for further improvement of teaching methodology and scientific research. Materials and methods of the study – general scientific, special and interdisciplinary methods based on the principles of historicism, scientificity and objectivity in the coverage of events which formed the methodological basis of the study. General scientific methods such as synthesis, analysis, induction and deduction were used to define the object and subject, the purpose, and conclusions were formulated. Descriptive statistics allowed us to process the data to ensure accuracy and relevance to the problem under study. The article highlights the “life path” of the Department of Skin and Venereal Diseases of Dnipro State Medical University from the moment of creation and formation of the scientific school to the “modern life of the department”. The authors try to strictly adhere to the principle of historicism, events and facts are considered in chronological order, taking into account the peculiarities of the circumstances and the flow of historical time for the development of education and science. The methodological basis of the study is based on the following: scientific and objective approach to the sequence of historical events and their impact on the present, using a set of general scientific methods with an interdisciplinary approach. The authors draw attention to the formation of medical science as a complex process and the importance of the discipline “History of Medicine” in covering the events of this process, the impact on medical students and the transformation in the field of medical research. In the historical development of the department, four periods were identified, which were compared with the areas of art, given that the word “Medicine” (Latin medicina) comes from the phrase “ars medicina” – the art of treatment, healing: The period of “medical ‘abstractionism’; The period of ‘medical modernism’; The period of ‘medical revival’; The period of ‘medical constructivism’. It was found that the historical development of the department follows the philosophical laws of the development of science by T. Kuhn and I. Lakatos. For the first time, the department was defined in terms of philosophy and its driving force in both formal and informal terms. The criteria and conditions for the creation of scientific schools are proved, and it is also proved that the life cycle of a department is longer than that of scientific schools. The importance of a leader in the life of a department and a scientific school is emphasized. It is emphasized that the main components of a leader are: charisma, strategic thinking, the desire for self-development, active scientific activity, and that these components contribute to the formation of medical science, improvement of methodological work in the educational activities of scientists and, as a result, the formation of the scientific and medical elite of the state.